Remote working and occupational stress: Effects on IT-enabled industry employees in Hyderabad Metro, India - Prasad, K.D.V.; Vaidya, Rajesh; Rani, Ridhi (Frontiers in Psychology, 2023)
The researchers report the outcome of an empirical study on remote working and occupational stress and its effect on employee job satisfaction, motivation, and performance. Remote working has three sub-scales self-proficiency, technology, and teamwork, whereas intrinsic and extrinsic motivation sub-scales are included to assess employee motivation. Five hundred thirteen (513) responses concerning remote working sub-scales employee self-proficiency, technology, teamwork, and occupational stress, the independent variables’ effect on the dependent variables job satisfaction, intrinsic motivation, extrinsic motivation, and performance were assessed. The measured Cronbach’s alpha is in the range of 0.64 to 0.77 demonstrating the reliability and internal consistency of the research instrument. The general linear model results indicate all the independent variables self-proficiency, teamwork, job stress are statistically significant and are influencing the outcome variables. The general linear model results further indicate statistically significant age differences on dependent variables, however, there were no statistically significant gender differences. The independent variable self-proficiency influencing job satisfaction, intrinsic motivation, and performance (p<0.01); teamwork is influencing employee job satisfaction and extrinsic motivation (p<0.01; p<0.05); job stress on performance (p<0.01) are statistically significant and influencing the outcome variables. However, the model predicted a statistically significant influence of age (p<0.01) on all the dependent factors job satisfaction, intrinsic motivation, extrinsic motivation and performance.